Harmful algal blooms: new methods of control and management. (22nd April 2008) - Mattei, Daniela; Salvatore, Giuseppe; Bruno, Milena
The general increase in eutrophication of waters and the changes in global climatic conditions have caused over the last 30 years the spread of algal blooms in seas all over the world. The paper describes the different aspects of this problem, the known classes of marine algal toxins and their effects on human activities, and the problem of ballast waters. New strategies of remote sensing control, informative medical net projects and methods of managing and avoiding the related health consequences are also discussed.